Energy-efficient power allocation algorithm based on the BFGS algorithm and the armijo criterion - Gao, Yunbo; Wang, Guorong; Li, Cuiran; Li, Maoqing; Cheng, Xuan (Sustainable energy technologies and assessments, 2023)
In high-speed railway (HSR), the increasing demand for wireless communication and high-speed broadband leads to higher energy consumption by the system. To improve energy efficiency (EE) and fair allocation of resources in multi-user communication, an algorithm combining the BFGS algorithm and the Armijo criterion is used. Firstly, an EE optimisation model of the system is constructed by considering the constraints, such as the average transmitting power of the evolved Node B (eNB), the minimum transmission rate and fairness among users. Secondly, the objective function is transformed into a convex optimisation problem through equivalent transformation. Finally, an algorithm combining the BFGS algorithm and the Armijo criterion is used to solve the objective function and then determine the power allocation scheme for each moment of the system. The simulation results show that the proposed scheme shows a better performance in terms of EE than the traditional algorithm in the same scenario over time. Under different user numbers and proportional rate constraint conditions, the adopted scheme can optimise system EE while satisfying the user communication fairness threshold. In addition, compared with the traditional power allocation scheme, the proposed algorithm is significantly improved in terms of eNB transmit power, fairness and EE performance.